(untitled) (Academicia Globe: Inderscience Research, 2022)
In the article, the place of innovative technologies and ways of developing students’ linguistic, sociolinguistic, pragmatic and strategic competences within the framework of a communicative approach in teaching English with the help of technology, methodical support for the use of innovative technologies based on the development of independent education are analyzed.